Train Scheduling with Hybrid Answer Set Programming. Issue 3 (27th May 2021) - ABELS, DIRK; JORDI, JULIAN; OSTROWSKI, MAX; SCHAUB, TORSTEN; TOLETTI, AMBRA; WANKO, PHILIPP
Abstract: We present a solution to real-world train scheduling problems, involving routing, scheduling, and optimization, based on Answer Set Programming (ASP). To this end, we pursue a hybrid approach that extends ASP with difference constraints to account for a fine-grained timing. More precisely, we exemplarily show how the hybrid ASP system clingo [DL] can be used to tackle demanding planning and scheduling problems. In particular, we investigate how to boost performance by combining distinct ASP solving techniques, such as approximations and heuristics, with preprocessing and encoding techniques for tackling large-scale, real-world train-scheduling instances.